CYBER SECURITY THREATS; ANALISIS DAN MITIGASI RESIKO RANSOMWARE DI INDONESIA - Novita, Aliya Putri; Fatmanegara, Fahmi; Runtuwene, Faithly Jabez Jefune; Samuela, Joeanna Talita; Syahbani, Muhammad Fahri (Jurnal Ilmiah Sistem Informasi, 2023)
Ransomware is a type of malware that encrypts a victim's data and demands a ransom payment for its decryption. These attacks can cause significant financial losses, disrupt business operations, and compromise sensitive data. Therefore, it is crucial to understand the mechanisms of ransomware and implement appropriate preventive measures. Preventive Measures against Ransomware Attacks; First, strengthen infrastructure security: Implement best practices such as firewalls, antivirus software, and data encryption to safeguard systems. Second, enhance employee security awareness: Provide cybersecurity training to employees to help them identify and avoid ransomware threats. third, maintain comprehensive and up-to-date data backups: Regularly back up data to ensure its recovery in the event of an attack. Forth, promptly update software and operating systems: Apply software and OS updates to patch security vulnerabilities. By adopting these measures, individuals and organizations can significantly enhance their cybersecurity posture and mitigate the risk of ransomware attacks